Application of the Project Based Learning Model to Improve Students' Short Story Writing Skills - Misnawati, Misnawati; Arwan, Arwan; Ikra, Ikra; Suryaningsih, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Writing short stories is one of the materials taught at the high school level, so short story writing skills must be developed using a learning model that supports this. The aim of this study is to improve students' short story writing skills after implementing the PjBL model. The method used in this research is quantitative experimental research pre-experimental design. Sampling using random sampling technique with a sample of 7 class X students of SMA Muhammadiyah Bolo. The data collection instrument used a short story writing skills test which was then processed using an n-gain test to see the improvement. The results of the study showed that there was an increase in short story writing skills in class X students of SMA Muhammadiyah Bolo after the implementation of the PjBL model with a classification of 28.5% of students in the high category, 57.3% in the medium category, and 14.29% in the low category.